Deep Brain Stimulation Improves the Symptoms and Sensory Signs of Persistent Central Neuropathic Pain from Spinal Cord Injury: A Case Report - Jermakowicz, Walter J.; Hentall, Ian D.; Jagid, Jonathan R.; Luca, Corneliu C.; Adcock, James; Martinez-Arizala, Alberto; Widerström-Noga, Eva (Frontiers in Human Neuroscience, 2017)
Central neuropathic pain (CNP) is a significant problem after spinal cord injury (SCI). Pharmacological and non-pharmacological approaches may reduce the severity, but relief is rarely substantial. While deep brain stimulation (DBS) has been used to treat various chronic pain types, the technique has rarely been used to attenuate CNP after SCI. Here we present the case of a 54-year-old female with incomplete paraplegia who had severe CNP in the lower limbs and buttock areas since her injury 30 years prior. She was treated with bilateral DBS of the midbrain periaqueductal gray (PAG). The effects of this stimulation on CNP characteristics, severity and pain-related sensory function were evaluated using the International SCI Pain Basic Data Set, Neuropathic Pain Symptom Inventory, Multidimensional Pain Inventory and Quantitative Sensory Testing before and periodically after initiation of DBS. After starting DBS treatment, weekly CNP severity ratings rapidly decreased from severe to minimal, paralleled by a substantial reduction in size of the painful area, reduced pain impact and reversal of pain-related neurological abnormalities, i.e., dynamic-mechanical and cold allodynia. She discontinued pain medication on study week 24. The improvement has been consistent. The present study expands on previous findings by providing in-depth assessments of symptoms and signs associated with CNP. The results of this study suggest that activation of endogenous pain inhibitory systems linked to the PAG can eliminate CNP in some people with SCI. More research is needed to better-select appropriate candidates for this type of therapy. We discuss the implications of these findings for understanding the brainstem’s control of chronic pain and for future progress in using analgesic DBS in the central gray.